PERLINDUNGAN HUKUM PEMBELI ATAS JUAL BELI TANAH YANG TIDAK DISERTAI AKTA PPAT TERKAIT BALIK NAMA SERTIPIKAT - Handoko, Mukhlas; Putra Hutomo; Yagus Suyadi (Journal of Innovation Research and Knowledge, 2025)
Land sale and purchase transactions conducted without a Land Deed Official’s Sale and Purchase Deed (PPAT Deed) can give rise to legal issues when registering the transfer of land title, as such transfer requires the PPAT Deed as a formal prerequisite. The research problems are: (1) What are the legal consequences of land sale and purchase transactions conducted without a PPAT Deed; and (2) What regulations provide legal protection to buyers in such transactions in relation to the registration of land title transfers. The theories applied are Satjipto Rahardjo’s theory of legal protection and R. Subekti’s theory of legal consequences. This study employs a normative juridical research method, namely legal research based on library studies or secondary data, consisting of primary, secondary, and tertiary legal sources. The research approach includes statutory, case, analytical, and conceptual approaches. Legal materials were collected by identifying and inventorying positive legal rules, books, journals, and other legal references. The analysis was conducted using grammatical interpretation, systematic interpretation, and the methods of analogy construction and legal refinement. The findings show that the legal consequence of a land sale and purchase conducted without a PPAT Sale and Purchase Deed remains valid under civil law insofar as it fulfills the validity requirements of agreements under the Indonesian Civil Code; however, such transactions do not result in a juridical and administrative transfer of land rights. Under the applicable legal framework, buyers must first submit an application to the court for the issuance of a PPAT Deed in order to obtain legal protection for the validity of the transaction, thereby granting authority to the PPAT to formally execute the deed.